Equity and quality practices at the Universidad Veracruzana, Campus Poza Rica - Villalobos López, Marilú (2020)
Despite the progress that humanity has made in different spheres, it has no yet been possible to guarantee universal human rights or providing quality of life to all the humanity. An aspect that becomes key is equity and, when the absence of equity occurs in an educational institution; its quality is also affected. For this reason this wrinting shows results obtained from a research on Equity and Quality as part of the European Project ORACLE 2019 (Regional Observatory of Quality of Equity or Higher Education in Latin America) carried out at the Universidad Veracruzana in its Poza Rica – Tuxpan Region. For this report, specifically presents the results obtained in the Faculty or Architecture. This research was intended to know the practices of equity and quality that are observed in said institution from the perspective of the teaching staff and students.